2004
DOI: 10.1016/j.virol.2004.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of viruses infecting ectothermic animals by amphibian and piscine antimicrobial peptides

Abstract: The ability of five purified amphibian antimicrobial peptides (dermaseptin-1, temporin A, magainin I, and II, PGLa), crude peptide fractions isolated from the skin of Rana pipiens and R. catesbeiana, and four antimicrobial peptides (AMPs) from hybrid striped bass (piscidin-1N, -1H, -2, and -3) were examined for their ability to reduce the infectivity of channel catfish virus (CCV) and frog virus 3 (FV3). All compounds, with the exception of magainin I, markedly reduced the infectivity of CCV. In contrast to CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
122
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(124 citation statements)
references
References 40 publications
1
122
0
1
Order By: Relevance
“…Viral mRNA is detectable in the intestines of larval and adult African clawed frogs ( Xenopus laevis ) as early as 3 h after exposure to virus in water and then spreads to other tissues, suggesting that the intestines are a primary point of entry of waterborne virus in amphibians (Robert et al 2011 ). The skin may not be a common site of infection in metamorphosed amphibians because they secrete antimicrobial peptides on their skin, which can inactivate several types of pathogens, including FV3 and ATV (Chinchar et al , 2004Sheafor et al 2008 ; Rollins-Smith 2009 ). Brunner et al ( 2007 ), however, demonstrated that a 1 s skinto-skin contact out of water was suffi cient for transmission of ATV from infected, symptomatic tiger salamander larvae to uninfected larvae, so entry through the epithelium is possible at least during the larval stage.…”
Section: Ranavirus Transmission Within a Speciesmentioning
confidence: 99%
“…Viral mRNA is detectable in the intestines of larval and adult African clawed frogs ( Xenopus laevis ) as early as 3 h after exposure to virus in water and then spreads to other tissues, suggesting that the intestines are a primary point of entry of waterborne virus in amphibians (Robert et al 2011 ). The skin may not be a common site of infection in metamorphosed amphibians because they secrete antimicrobial peptides on their skin, which can inactivate several types of pathogens, including FV3 and ATV (Chinchar et al , 2004Sheafor et al 2008 ; Rollins-Smith 2009 ). Brunner et al ( 2007 ), however, demonstrated that a 1 s skinto-skin contact out of water was suffi cient for transmission of ATV from infected, symptomatic tiger salamander larvae to uninfected larvae, so entry through the epithelium is possible at least during the larval stage.…”
Section: Ranavirus Transmission Within a Speciesmentioning
confidence: 99%
“…Mucus performs a variety of functions (besides inhibition of the invasion and proliferation of pathogenic microorganism) including ion regulation, osmoregulation, lubrication [8,65,81,100], and parenteral care behaviour [101]. The antimicrobial property of epidermal mucus against infectious pathogens (bacteria and viruses) has been demonstrated in different fish species [8,84,[102][103][104][105], and increased expression of one or more of the above-mentioned antimicrobial components in fish epidermal mucus has been observed following microbial stress [106,107], thus supporting the role of epidermal mucus in protecting fishes from infectious pathogens.…”
Section: The Cutaneous Mucus Layermentioning
confidence: 99%
“…chrysops). [12][13][14] Piscidin is a 22-residue peptide with a highly conserved amino-terminus rich in histidine and phenylalanine. Piscidins are composed of piscidin 1 (P1), 2 (P2), and 3 (P3), and these peptides play important roles in the natural innate immune system of fish.…”
mentioning
confidence: 99%
“…Piscidins have broad-spectrum activities against yeast, filamentous fungi, viruses, and bacteria, including antibiotic-resistant bacteria and of all piscidins, P1 has the highest biological activity, while P3 has the lowest. 13,14) Also, its mechanism of action against bacteria was defined as that piscidin is more likely to permeabilize the membrane by toroidal pore formation rather than via the "barrel-stave" mechanism. 15) However, their exact mode of fungicidal action remains unknown.…”
mentioning
confidence: 99%